Cultural dimensions of Anglos, Australians and Malaysians / Asma Abdullah - Abdullah, Asma (Faculty of Business and Management ; UiTM Press, 2005)
This paper seeks to investigate the similarities and differences in the cultural dimensions among Anglos, Australians, and Malaysians, which comprise of Chinese, Indians, and Malays. The main results reveal that the Anglos and the Australians differed significantly from the Malaysians in six dimensions. The most significant differences occur in dimensions related to relationships, collectivism, and religiosity. Among the Malaysian groups, there is only one significant difference. This occurs in the religiosity dimension, whereby the Malays differ from the Chinese and the Indians. The research discusses these differences and considers some suggestions for studying Malaysian managerial behaviors.